Preliminary Research for Fault Identification as Disaster Mitigation in Sumbawa Besar Using Geophysics and Geology Methods - Hayatuzzahra, Sayidatina; Jayatri, Adella Ulyandana; Desiasni, Rita (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2024)
Faults are conditions under which rocks are displaced from their original positions. Its presence is closely related to its high tectonic activity. Fault movement can trigger earthquake disasters. Therefore, various studies on faults are important for carrying out disaster mitigation efforts. This study aims to identify the existence of faults in Sumbawa Besar as a disaster mitigation effort. The method used was a combination of geophysical methods and geological field observations. Geophysical methods include the average shear wave method (VS30) and the gravity method. The geological method consists of direct geological observations (geomorphology and structural geology) in the research area. The results of research based on geophysical methods, namely the gravity method, showed that in the research area, there were indications of thrust faults, which were then strengthened by VS30 analysis, which showed the existence of weak zones along the suspected fault lines. The results of field data collection and geological data analysis show that no surface fault characteristics were found in the research area.